Revival and awakening : American evangelical missionaries in Iran and the origins of Assyrian nationalism - Becker, Adam H., 1972- (The University of Chicago Press, 2015)
This volume examines how the presence of an American evangelical mission in the borderlands between Qajar Iran and the Ottoman Empire in the nineteenth century contributed to the development of a secular nationalism among the indigenous Neo-Aramaic speaking Christian population of the region. A particular evangelical configuration of modernity was cultivated at the mission in the antebellum period, one belonging to a visceral realm often unrecognised in characterisations of secularism and the Enlightenment.